High-energy-storage sodium bismuth titanate-based lead-free relaxation type ferroelectric thick-film ceramic as well as preparation method and application of high-energy-storage sodium bismuth titanate-based lead-free relaxation type ferroelectric thick-film ceramic

By doping BaTiO3, SrTiO3 and Bi(Mg0.5Zr0.5)O3 in sodium bismuth titanate ceramics, a ferroelectric thick film ceramic with a specific chemical composition is solved, and the energy storage density and efficiency of existing sodium bismuth titanate ceramics are solved. The poor problem has achieved high energy storage density and high efficiency ceramic materials.

CN119462139APending Publication Date: 2025-02-18GUANGDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411348150.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing bismuth sodium titanate ceramics have poor performance in energy storage density and energy storage efficiency, and their coercive electric field and residual polarization strength are high, resulting in unsatisfactory energy storage performance of the substrate.

Method used

Through component regulation, BaTiO3, SrTiO3 and Bi(Mg0.5Zr0.5)O3 are doped into bismuth sodium titanate ceramic to form (0.74-x)Bi0.5Na0.5TiO3-0.06BaTiO3-0.2SrTiO3-xBi(Mg0.5Zr0 .5) The chemical composition of O3 improves its energy storage density and energy storage efficiency.

Benefits of technology

The energy storage density reaches more than 11J/cm3, the energy storage efficiency reaches more than 85%, and good stability is maintained in a wide temperature range and wide frequency range, which significantly improves the energy storage performance of ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462139A_ABST
    Figure CN119462139A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramics, and discloses a high-energy-storage sodium bismuth titanate-based lead-free relaxation type ferroelectric thick film ceramic as well as a preparation method and application thereof, the chemical formula of the ferroelectric ceramic is (0.74-x) Bi < 0.5 > Na < 0.5 > TiO < 3 >-0.06 BaTiO < 3 >-0.2 SrTiO < 3-x > Bi (Mg < 0.5 > Zr < 0.5 >) O < 3 >, and x is greater than or equal to 0.18 and less than or equal to 0.25. The ceramic has the advantages of high energy storage density, large saturation polarization intensity, low remanent polarization intensity, high breakdown-resistant electric field intensity, good temperature stability and good frequency stability. The energy storage density of the ferroelectric ceramic is above 11J / cm < 3 >, the energy storage efficiency is above 85%, and the ferroelectric ceramic can be applied to high-power pulse devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional ceramic materials and relates to a sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with high energy storage, and a preparation method and application thereof. Background Art

[0002] The needs of social development have promoted the development of energy storage technology and increased the demand for energy supply, and clean and efficient energy storage capacitors have emerged. Dielectric functional ceramics are suitable for scenarios requiring high instantaneous power due to their excellent power density, extremely short charge and discharge time, long cycle life, and strong safety and stability. They are mainly used in military and medical fields. However, the energy storage performance of commercial mass-produced dielectric capacitors in daily life is generally less than 2J / cm 3 , so it is meaningful to develop dielectric capacitors with higher energy storage density and higher energy storage efficiency.

[0003] Generally speaking, the total energy storage density (W tot ), recoverable energy storage density (W rec ) and energy storage efficiency (η) can be calculated through the PE hysteresis loop according to formulas (1)–(3):

[0004]

[0005]

[0006]

[0007] Where P m , P r and E represent the saturation polarization intensity, residual polarization intensity and external electric field, respectively. As shown in the above formula, high dielectric breakdown field strength and large ΔP (P m -P r ) are two key factors in achieving high energy storage performance of dielectric materials. If high energy storage density is required, a high W rec , high η and good working stability.

[0008] Although pure sodium bismuth titanate ceramics have a high maximum polarization intensity P max However, due to its high coercive electric field and high residual polarization intensity, the energy storage density and energy storage efficiency of the matrix are not good. Therefore, in order to obtain a higher energy storage density and efficiency at a certain temperature, sodium bismuth titanate ceramics are doped and modified, and excellent wide temperature range energy storage performance is also obtained, which has important practical significance for the application in the field of electronic equipment at normal temperature. Summary of the invention

[0009] In order to solve the above-mentioned deficiencies and shortcomings in the prior art, the primary purpose of the present invention is to provide a high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic. The ferroelectric thick film ceramic improves the energy storage density and energy storage efficiency of the sodium bismuth titanate ceramic system by controlling the composition, and at the same time obtains good stability in a wide temperature range and wide frequency.

[0010] Another object of the present invention is to provide a method for preparing the above-mentioned sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic.

[0011] Another object of the present invention is to provide an application of the above-mentioned sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic.

[0012] The purpose of the present invention is achieved through the following technical solutions:

[0013] A high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with a chemical formula of (0.74-x)Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-xBi(Mg 0.5 Zr 0.5 )O3, where x represents the mole fraction, 0.18≤x≤0.25.

[0014] Preferably, the energy storage density of the ferroelectric ceramic is 11 J / cm 3 The above energy storage efficiency is above 85%, and the thickness of the ferroelectric ceramic is 22 to 28 μm.

[0015] More preferably, the chemical formula of the ferroelectric ceramic is 0.52Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.22Bi(Mg 0.5 Zr 0.5 )O3.

[0016] More preferably, the energy storage density of the ferroelectric ceramic is 15.79 J / cm 3 , the energy storage efficiency is 92.86%.

[0017] The method for preparing the high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic comprises the following steps:

[0018] S1. Na2CO3, Bi2O3, BaCO3, TiO2, SrCO3, ZrO2 and MgO are uniformly mixed to obtain a ceramic powder;

[0019] S2. The ceramic powder is calcined at 845-855°C, and then naturally cooled in the furnace. The pre-calcined powder is mixed with a solvent, a binder and a plasticizer, and a slurry is obtained by ball milling. The slurry is coated on a polyethylene glycol film and dried to obtain a thick film green tape;

[0020] S3. The thick film green tape is first heated to 595-605°C and kept warm, then heated to 1145-1205°C for sintering, and then cooled to 1065-1205°C to obtain a sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with high energy storage.

[0021] Preferably, the calcination time in step S2 is 3 to 4 hours, the insulation time in step S3 is 1 to 6 hours, and the sintering time is 4 to 5 hours.

[0022] Preferably, the solvent in step S2 is ethanol and butanone in a mass ratio of 1:1, the binder is polyvinyl butyral, and the plasticizer is dibutyl phthalate.

[0023] The application of the high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic in high power pulse devices.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of the present invention is (0.74-x)Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-xBi(Mg 0.5 Zr 0.5 )O3. The energy storage density of this ceramic is 11J / cm 3 The energy storage efficiency is above 85%. Multi-ion doping breaks the association between adjacent dipoles and long-range ordered ferroelectricity, that is, increases long-range structural disorder and converts macroscopic or microscopic domains into nanoscopic domains. Bi(Mg 0.5 Zr 0.5 )The addition of O3 enables the coexistence of rhombohedral and tetragonal phases in the ceramic, while also reducing the grain size, increasing the grain boundary density, and making the ceramic denser, which will help improve the breakdown field strength. It also increases the randomness of the oxygen octahedron tilt, causing the combined polarization and delayed polarization to saturate, and the average breakdown field strength increases from 717.67 kV / cm in the first component (x=0.18) to 1082.16 kV / cm in the preferred group (x=0.22). After the preferred group, it decreases with the increase in the doping amount. The maximum energy storage density of 15.79 J / cm was obtained in the preferred group (x=0.22). 3The efficiency is 92.86%. In the variable temperature range (20-160°C), as the temperature increases, the efficiency stabilizes at 90.73%-94.11%, with a deviation of 3.38%, and its temperature stability is excellent; in the frequency range of 1-200Hz, W rec The change is only 2.56%, which proves that it has good frequency stability.

[0026] 2. The present invention adopts powder mixing, drying and screening, tape casting and sintering, and the production process is simple, no difficult process requirements are required, the raw materials do not contain lead, rare earth elements and precious metals, the raw materials are cheap, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The X-ray diffraction pattern of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 1-4;

[0028] Figure 2 The scanning electron microscope image of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 1-4;

[0029] Figure 3 The dielectric temperature spectrum of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 1-4;

[0030] Figure 4 PE single hysteresis loops of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics prepared in Examples 1-4 measured at 20° C. (standard atmospheric pressure) under respective larger electric fields;

[0031] Figure 5 This is a diagram of energy storage performance of sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics prepared in Examples 1-4;

[0032] Figure 6 The energy band transition energy diagrams of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics and pure sodium bismuth titanate prepared in Examples 1, 3, and 4;

[0033] Figure 7 The impedance test analysis diagram of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 1-4 at 450° C. and 100-2 MHz;

[0034] Figure 8 PE single hysteresis loop and energy storage performance of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 3;

[0035] Fig. 9 The underdamping curve of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 3 at 20° C. (standard atmospheric pressure) as the electric field changes;

[0036] Fig.10 This is a graph showing the variation of discharge energy storage density with electric field at 20°C (standard atmospheric pressure) for the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 3. DETAILED DESCRIPTION

[0037] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0038] Example 1

[0039] 1. Analytically pure Na2CO3, Bi2O3, BaCO3, TiO2, SrCO3, ZrO2 and MgO powders were mixed at 0.56Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.18Bi(Mg 0.5 Zr 0.5 )O3 stoichiometric ratio is weighed, anhydrous ethanol is used as the medium, zirconium balls are added, and a planetary ball mill is used to mix at a speed of 250 rpm for 24 hours. The obtained slurry is filtered through the zirconium balls and placed in an oven at 80°C for drying and passed through a 40-mesh sieve to obtain ceramic powder.

[0040] 2. The ceramic powder was placed in a muffle furnace and pre-fired at 850℃ for 3 hours to obtain pre-fired powder. The pre-fired powder was ball-milled with a solvent (the mass ratio of ethanol and butanone was 1:1, and the mass ratio of pre-fired powder to solvent was 1:2), a binder (polyvinyl butyral) and a plasticizer (dibutyl phthalate) to obtain a uniformly dispersed slurry, which was then coated on a polyethylene glycol (PET) film. Then, it was dried at different temperature zones of 40℃±0.5℃, 45℃±0.5℃, and 30℃±0.5℃ to obtain a smooth and uniform thick film green tape.

[0041] 3. The thick film green tape was sintered in a muffle furnace in two steps. The temperature was first raised to 600℃ and kept for 6 hours, then raised to the highest temperature of 1200℃ and kept for 1 hour, and then lowered to 1120℃ and kept for 4 hours. After the furnace cavity was cooled, 0.56Bi was obtained. 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.18Bi(Mg 0.5 Zr 0.5 )O3, which is a high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with a thickness of 24.95±0.14μm and an energy storage density of 11.27J / cm 3 , the energy storage efficiency is 87.28%.

[0042] Example 2

[0043] 1. Analytically pure Na2CO3, Bi2O3, BaCO3, TiO2, SrCO3, ZrO2 and MgO powders were mixed at 0.54Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.20Bi(Mg 0.5 Zr 0.5 )O3 stoichiometric ratio was weighed, anhydrous ethanol was used as the medium, zirconium balls were added and ball milled at 250 rpm for 24 h in a planetary ball mill to mix evenly, the zirconium balls were filtered out of the obtained slurry, and then the slurry was placed in an oven at 80°C for drying and passed through a 40-mesh sieve to obtain ceramic powder.

[0044] 2. The ceramic powder was placed in a muffle furnace and pre-fired at 850℃ for 3 hours to obtain pre-fired powder. The pre-fired powder was ball-milled with a solvent (the mass ratio of ethanol and butanone was 1:1, and the mass ratio of pre-fired powder to solvent was 1:2), a binder (polyvinyl butyral) and a plasticizer (dibutyl phthalate) to obtain a uniformly dispersed slurry, which was then coated on a polyethylene glycol (PET) film. Then, it was dried at different temperature zones of 40℃±0.5℃, 45℃±0.5℃, and 30℃±0.5℃ to obtain a smooth and uniform thick film green tape.

[0045] 3. The thick film green tape was sintered in a muffle furnace in two steps. The temperature was first raised to 600℃ and kept for 6 hours, then raised to the highest temperature of 1180℃ and kept for 1 hour, and then lowered to 1100℃ and kept for 4 hours. After the furnace cavity was cooled, 0.54Bi was obtained. 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.20Bi(Mg 0.5 Zr 0.5 )O3, which is a high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with a thickness of 22.65±0.17μm and an energy storage density of 14.36J / cm 3 , the energy storage efficiency is 85.71%.

[0046] Example 3

[0047] 1. Analytically pure Na2CO3, Bi2O3, BaCO3, TiO2, SrCO3, ZrO2 and MgO powders were mixed at 0.52Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.22Bi(Mg 0.5 Zr 0.5)O3 stoichiometric ratio was weighed, anhydrous ethanol was used as the medium, zirconium balls were added and ball milled at 250 rpm for 24 h in a planetary ball mill to mix evenly, the obtained slurry was filtered through the zirconium balls and then placed in an oven at 80°C for drying and passed through a 40-mesh sieve to obtain ceramic powder.

[0048] 2. The ceramic powder was placed in a muffle furnace and pre-fired at 850℃ for 3 hours to obtain pre-fired powder. The pre-fired powder was ball-milled with a solvent (the mass ratio of ethanol and butanone was 1:1, and the mass ratio of pre-fired powder to solvent was 1:2), a binder (polyvinyl butyral) and a plasticizer (dibutyl phthalate) to obtain a uniformly dispersed slurry, which was then coated on a polyethylene glycol (PET) film. Then, it was dried at different temperature zones of 40℃±0.5℃, 45℃±0.5℃, and 30℃±0.5℃ to obtain a smooth and uniform thick film green tape.

[0049] 3. The thick film green tape was sintered in a muffle furnace in two steps. The temperature was first raised to 600°C and kept for 6 hours, then raised to the highest temperature of 1150°C and kept for 1 hour, and then lowered to 1070°C and kept for 4 hours. After the furnace cavity was cooled, 0.52Bi was obtained. 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.22Bi(Mg 0.5 Zr 0.5 )O3, which is a high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with a thickness of 27±0.12μm and an energy storage density of 15.79J / cm 3 , the energy storage efficiency is 92.86%.

[0050] Example 4

[0051] 1. Analytically pure Na2CO3, Bi2O3, BaCO3, TiO2, SrCO3, ZrO2 and MgO powders were mixed at 0.49Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.25Bi(Mg 0.5 Zr 0.5 )O3 stoichiometric ratio was weighed, anhydrous ethanol was used as the medium, zirconium balls were added and mixed evenly by ball milling for 24 hours, and this step used a planetary ball mill at a speed of 250 rpm. The obtained slurry was filtered through the zirconium balls and placed in an oven at 80°C for drying, and passed through a 40-mesh sieve to obtain ceramic powder.

[0052] 2. The ceramic powder was placed in a muffle furnace and pre-fired at 850℃ for 3 hours to obtain pre-fired powder. The pre-fired powder was ball-milled with a solvent (the mass ratio of ethanol and butanone was 1:1, and the mass ratio of pre-fired powder to solvent was 1:2), a binder (polyvinyl butyral) and a plasticizer (dibutyl phthalate) to obtain a uniformly dispersed slurry, which was coated on a polyethylene glycol (PET) film. Then, it was dried at different temperature zones of 40℃±0.5℃, 45℃±0.5℃, and 30℃±0.5℃ to obtain a smooth and uniform thick film green tape.

[0053] 3. The thick film green tape was sintered in a muffle furnace in two steps. The temperature was first raised to 600°C and kept for 6 hours, then raised to the highest temperature of 1150°C and kept for 1 hour, and then lowered to 1070°C and kept for 4 hours. After the furnace cavity was cooled, 0.49Bi was obtained. 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.25Bi(Mg 0.5 Zr 0.5 )O3 ceramics, namely, high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics, with a thickness of 25.25±0.22μm and an energy storage density of 11.89J / cm 3 , the energy storage efficiency is 85.52%.

[0054] Gold electrodes were sputtered on both sides of the thick film ceramics obtained in Examples 1-4, and various physical and electrical tests were performed. Figure 1 The X-ray diffraction diagram of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics prepared in Examples 1-4 shows that all ceramics do not contain perovskite structures with other impurity phases. 0.5 Zr 0.5 ) As the O3 content increases, the diffraction front near 45° moves to a lower diffraction angle, and the asymmetric single peak gradually evolves into a weak splitting front, and multi-phase coexistence occurs. This is because the magnesium and zirconium elements with large ionic radius enter the lattice and replace the original titanium element.

[0055] Figure 2 The surface morphology and corresponding actual thickness electron microscope images of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics of Examples 1-4. (a)-(d) are the actual thickness electron microscope measurement images of x=0.18, 0.20, 0.22, and 0.25, respectively; (e)-(h) are the surface morphologies of x=0.18, 0.20, 0.22, and 0.25, respectively. Figure 2 It can be seen that the grain structure of all ceramics is uniform and dense with clearly discernible grain boundaries, the grain size is uniform, the average grain size is 1 to 3 μm, and the relative density of the ceramics is more than 97%.

[0056] Figure 3The dielectric temperature spectrum of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Examples 1-4. Figure 3 It can be seen that the dielectric constant-temperature peak moves to low temperature with the increase of frequency, and the dielectric peak shifts to high temperature at T. As the frequency increases, the peak decreases, showing the characteristic linearity of typical relaxor ferroelectrics. At the same time, a low temperature side peak (T s ) and high temperature side peak (T m ) two dielectric constant peaks. The low temperature side peak is due to the thermal evolution of the polar nano-microregions of the rhombohedral phase (space group R3c) and tetragonal phase (space group P4bm) structures. The high temperature side peak is due to the thermal evolution of the polar nano-microregions of the tetragonal phase structure. 0.5 Zr 0.5 )O3 content increases, T m From 329℃ to low temperature to 266℃.

[0057] Figure 4 The PE single hysteresis loops of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics of Examples 1-4 were measured at 20°C (under standard atmospheric pressure) under respective large electric fields. Figure 4 It can be seen that as Bi(Mg 0.5 Zr 0.5 )With the increase of O3 content, the residual polarization intensity decreases continuously, while the saturation polarization intensity first increases and then decreases with the increase of x. The sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Example 3 reaches a maximum value, showing a typical relaxor ferroelectric hysteresis loop.

[0058] Figure 5 The energy storage performance diagram of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics of Examples 1-4. Figure 5 It can be seen that the energy storage performance increases first and then decreases with the increase of x. The sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Example 3 (when x=0.22) obtains 15.79 J / cm under an electric field of 1072.1 kV / cm 3 The energy storage density and energy storage efficiency of 92.86% are achieved, resulting in the optimal energy storage performance.

[0059] Figure 6 The energy band transition energy diagrams of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramics and pure sodium bismuth titanate prepared in Examples 1, 3, and 4 are shown in FIG. Figure 6 It can be seen that as x increases, the band gap width of the material continues to increase. Figure 7 The impedance test analysis diagram of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Examples 1-4 at 450°C and 100-2 MHz. Part of the circuit diagram is an equivalent circuit diagram. Figure 7As shown, the resistance of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Example 3 is the largest, indicating that the increase in impedance and the decrease in oxygen vacancy concentration are beneficial to the improvement of the breakdown field strength of the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic.

[0060] Figure 8 The PE single hysteresis loop and energy storage performance of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic prepared in Example 3. Among them, (a) is the PE single hysteresis loop that varies with frequency at a temperature of 20°C (standard atmospheric pressure) and an electric field of 600kV / cm; (b) is the PE single hysteresis loop that varies with temperature at an electric field of 10Hz and 600kV / cm; (c) is the PE single hysteresis loop that varies with the number of cycles at an electric field of 10Hz and 400kV / cm; (d) is the energy storage performance that varies with frequency at a temperature of 20°C (standard atmospheric pressure) and an electric field of 600kV / cm; (e) is the energy storage performance that varies with temperature at an electric field of 10Hz and 600kV / cm; (f) is the energy storage performance that varies with the number of cycles at an electric field of 10Hz and 400kV / cm. Figure 8 As shown in (a), the hysteresis loop shows a relatively thin shape in the range of 1Hz-200Hz; Figure 8 As shown in (b), the hysteresis loop shows a relatively slender shape in the range of 20-160°C (under standard atmospheric pressure), which shows that the sodium bismuth titanate-based lead-free relaxor ferroelectric has typical relaxor ferroelectric characteristics and relatively stable temperature stability. Figure 8 As shown in (c), the hysteresis loop of the thick film ceramic of Example 3 has no obvious change in its thin shape when the number of cycles is from 1 to 10000; Fig. 9 From (df), we can see that the frequency stability is high, the fluctuation is small (±1.98%), the temperature stability is excellent (±6.68%), and the fatigue stability is excellent (±1.10%).

[0061] Fig. 9 is the underdamping curve of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Example 3 at 20° C. (under standard atmospheric pressure) as the electric field changes; Fig. 9 It can be seen that at 55MV / m, I max Up to 16A. The time to restore equilibrium under all electric fields is short, with extremely fast response speed. Fig.10 The discharge energy storage density of the sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic of Example 3 changes with the electric field at 20°C (standard atmospheric pressure). Fig.10 It can be seen that the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramics of Example 3 have extremely fast discharge speeds under various electric fields at room temperature, with the fastest discharge speed reaching 44.0 nanoseconds under an electric field of 55MV / m, indicating that the sodium bismuth titanate-based lead-free relaxor ferroelectric ceramics have excellent energy storage properties and can be used in high-power pulse devices.

[0062] The present invention obtains a sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic by changing the composition. The ceramic has excellent energy storage performance and a power density of 582.47 MW / cm2 at room temperature with an applied electric field strength of 1072.10 kV / cm2. 3 And an ultra-fast discharge time of 44.0ns.

[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic, characterized in that: The chemical formula of the ferroelectric ceramic is (0.74-x)Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-xBi(Mg 0.5 Zr 0.5 )O3, where x represents the mole fraction, 0.18≤x≤0.

25.

2. The sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic according to claim 1, characterized in that: The energy storage density of the ferroelectric ceramic is 11 J / cm 3 The above energy storage efficiency is above 85%, and the thickness of the ferroelectric ceramic is 22 to 28 μm.

3. The sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic according to claim 1, characterized in that: The chemical formula of the ferroelectric ceramic is 0.52Bi 0.5 Na 0.5 TiO3-0.06BaTiO3-0.2SrTiO3-0.22Bi(Mg 0.5 Zr 0.5 )O3.

4. The sodium bismuth titanate-based lead-free relaxor ferroelectric ceramic according to claim 3, characterized in that: The energy storage density of the ferroelectric ceramic is 15.79 J / cm 3 , the energy storage efficiency is 92.86%.

5. The method for preparing the high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Na2CO3, Bi2O3, BaCO3, TiO2, SrCO3, ZrO2 and MgO are uniformly mixed to obtain a ceramic powder; S2. The ceramic powder is calcined at 845-855°C, and then naturally cooled in the furnace. The pre-calcined powder is mixed with a solvent, a binder and a plasticizer, and a slurry is obtained by ball milling. The slurry is coated on a polyethylene glycol film and dried to obtain a thick film green tape; S3. The thick film green tape is first heated to 595-605°C and kept warm, then heated to 1145-1205°C for sintering, and then cooled to 1065-1205°C to obtain a sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic with high energy storage.

6. The method for preparing the high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic according to claim 5, characterized in that: The calcination time in step S2 is 3 to 4 hours, the insulation time in step S3 is 1 to 6 hours, and the sintering time is 4 to 5 hours.

7. The method for preparing the high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic according to claim 5, characterized in that: The solvent in step S2 is ethanol and butanone in a mass ratio of 1:1, the binder is polyvinyl butyral, and the plasticizer is dibutyl phthalate.

8. Application of the high energy storage sodium bismuth titanate-based lead-free relaxor ferroelectric thick film ceramic according to any one of claims 1 to 4 in high power pulse devices.

Citation Information

Patent Citations

  • Sodium bismuth titanate-based relaxor ferroelectric ceramic material with wide temperature range and high electrocaloric effect as well as preparation method and application of sodium bismuth titanate-based relaxor ferroelectric ceramic material

    CN116813335A

  • High-energy-storage lead-free relaxor ferroelectric thick-film ceramic as well as preparation method and application thereof

    CN118307319A